2017
DOI: 10.1007/s00221-017-4884-9
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological evidence for enhanced attentional deployment in spatial learners

Abstract: Visual spatial attention is important during navigation processes that rely on a cognitive map, because spatial relationships between environmental landmarks need to be selected, encoded, and learned. People who navigate using this strategy are spatial learners, and this process relies on the hippocampus. Conversely, response learners memorize a series of actions to navigate, which relies on the caudate nucleus. Response learning, which is more efficient, is thought to involve less demanding cognitive operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 44 publications
3
20
0
Order By: Relevance
“…The groups did not significantly differ in terms of age (spatial: M = 22.68, SD = 3.91 yr; response: M = 24.28, SD = 4.96 yr; t (48) = 1.266, P = 0.212) or education (spatial: M = 15.60, SD = 1.89; response: M = 16.04, SD = 1.93; t (48) = 0.815, P = 0.419) or sex (χ 2 (1, N = 50) = 0.439, P= 0.508). As has been previously reported, response learners made significantly fewer probe errors associated with reduced landmark use during navigation: 22 response learners made no probe trial errors, whereas only eight spatial learners made no error (χ 2 (1, N = 50) = 16.333, P < 0.0001, Cramer's ϕ = 0.572) (Iaria et al 2003;Bohbot et al 2007;Konishi and Bohbot 2013;West et al 2015West et al , 2018Drisdelle et al 2017).…”
Section: Navigationsupporting
confidence: 72%
See 1 more Smart Citation
“…The groups did not significantly differ in terms of age (spatial: M = 22.68, SD = 3.91 yr; response: M = 24.28, SD = 4.96 yr; t (48) = 1.266, P = 0.212) or education (spatial: M = 15.60, SD = 1.89; response: M = 16.04, SD = 1.93; t (48) = 0.815, P = 0.419) or sex (χ 2 (1, N = 50) = 0.439, P= 0.508). As has been previously reported, response learners made significantly fewer probe errors associated with reduced landmark use during navigation: 22 response learners made no probe trial errors, whereas only eight spatial learners made no error (χ 2 (1, N = 50) = 16.333, P < 0.0001, Cramer's ϕ = 0.572) (Iaria et al 2003;Bohbot et al 2007;Konishi and Bohbot 2013;West et al 2015West et al , 2018Drisdelle et al 2017).…”
Section: Navigationsupporting
confidence: 72%
“…On the first trial, if participants reported using two or more landmarks to remember the location of the objects (e.g., going to the left of the tree, the two paths on the right of the rock and right in front of the mountain) and did not report using a sequence from a single starting point, they were categorized as spatial learners. If the participant reported using a sequence or pattern, counting from a single starting point (e.g., counting pathways starting from the tree, and then selecting Paths 1, 3, 5, and 6) to remember the locations of the objects, they were categorized as response learners (Iaria et al 2003;Bohbot et al 2007Bohbot et al , 2013Andersen 2011;Dahmani and Bohbot 2015;West et al 2015West et al , 2018Drisdelle et al 2017;Aumont et al 2019).…”
Section: On 8 Virtual Maze (4/8 Vm)mentioning
confidence: 99%
“…When learning a new environment, spatial learning requires more visual attention resources compared to response learning (Lindberg & Gärling, ). Supporting this observation, people who were categorized as spatial learners displayed increased visuospatial attention towards targets compared to response learners (Drisdelle et al, ). Further, eye‐tracking research found that spatial strategy use was associated with a greater number of fixations on landmarks when completing a navigation task compared to response learners (Andersen, Dahmani, Konishi, & Bohbot, ).…”
mentioning
confidence: 90%
“…Further, eye‐tracking research found that spatial strategy use was associated with a greater number of fixations on landmarks when completing a navigation task compared to response learners (Andersen, Dahmani, Konishi, & Bohbot, ). It is hypothesized that the spatial navigation strategy might impact the deployment of visuospatial attention by biasing attention to details in the environment that facilitate the constriction of an internal cognitive map (Drisdelle et al, ). Together, these results suggest that the autistic traits of hyper‐attention to detail and sensory hypersensitivity (Baron‐Cohen, Knickmeyer, & Belmonte, ; Baron‐Cohen et al, ) could support spatial strategy use and might explain observations of increased hippocampal grey matter in individuals who display such traits.…”
mentioning
confidence: 99%
See 1 more Smart Citation